Comparative study on the quality characters of winter onion (Allium cepa L.) varieties: Quality assessment of winter onion (Bangladesh Journal of Agriculture, 2024)
The experiment was conducted at Spices Research Sub-Centre (SRSC), Bangladesh Agricultural Research Institute (BARI), Faridpur, Bangladesh during 2021-22 to compare the quality characters of four existing winter onion varieties such as BARI Piaz-1, BARI Piaz-4, BARI Piaz-6 and Lal Teer King. The field and storage trial were laid out Randomized Complete Block Design (RCBD) and Completely Randomized Design (RCD), respectively. The results of the experiment revealed that the quality parameters studied were significant among the varieties except for the days to maturity of bulb. The BARI Piaz-4 had significantly the maximum dry yield (3.27t/ha) and the minimum bolting (11.51%) over other three varieties. The BARI Piaz-1 exhibited superior performance regarding dry matter, TSS, bulb firmness, pungency, storage loss and quantity and quality (texture/color) of Beresta (caramelized onions). The BARI Piaz-6 gave the best performance regarding incidence of split bulb and pungency. Lal Teer King performed best on the incidence of diseases. The BARI Piaz-1, BARI Piaz-6, BARI Piaz-4 and Lal Teer King expressed bronze red, followed by bronze red, pink red and light red skin color, respectively. The flesh color of bulb was reddish in BARI Piaz-4 and Lal Teer King. But BARI Piaz-1 and BARI Piaz-6 demonstrated white flesh color in bulb. Only BARI Piaz-4 had the torpedo shape while BARI Piaz-1, BARI Piaz-6 and Lal Teer King showed the similar shaped of bulbs like flat. The BARI Piaz-1, BARI Piaz-6, Lal Teer King gave highly crispy, crispy, light crispy and soft Beresta, respectively. The excellent (richly brown) and good (brown) colors of Beresta were observed in BARI Piaz-1 and BARI Piaz-6, respectively. However, the colors of Beresta for BARI Piaz-4 and Lal Teer King were very poor (darkish). This study's findings suggest that among the evaluated varieties, BARI Piaz-1 stands out due to its exceptional quality and beresta characteristics, although it exhibits lower yield. BARI Piaz-4, on the other hand, excels in terms of dry weight and displays minimal bolting tendencies. For those seeking pungency and reduced splitting, BARI Piaz-6 is the preferred choice. Lastly, when considering disease incidence, Lal Teer King demonstrates superior resistance.Bangladesh J. Agri. 2024, 49(1): 1-9